SUBSURFACE DRAINAGE IN KHUZESTAN, IRAN: ENVIRONMENTALLY REVISITED CRITERIA1. (18th June 2013) - Akram, Mojtaba; Azari, Ardavan; Nahvi, Ali; Bakhtiari, Zahra; Safaee, Heydar D.; Schultz, Bart
ABSTRACT Khuzestan, a south‐western province of Iran with a hot climate, long growing season and lots of water, is the main region of subsurface drainage. Sugar cane is the major artificially drained crop. In the past, drainage rates had been chosen based on highest water‐consuming crop in the cropping pattern. This approach neglects crops with less water demands, natural drainage and direct flow towards perforated collectors or open deep drains, and soil water reservoirs. The drains are installed deeply which bring more saline drainage water out of the underlying strata into the environment. The environmental problems are due to the high volume of very poor quality drainage water. The low irrigation efficiency results in a high volume of drainage water. Deeper drains are also responsible for over‐drainage because they usually work longer and bring mined salt water out of the deeper strata. This paper attempts to show that in arid areas with a long irrigation season and/or high deep percolation one does not have to expect secondary salinization provided that the leaching requirement is met. Maintaining higher irrigation efficiency, installation of shallower drains and the application of controlled drainage are measures to reduce salt removal, and hence reduce environmental hazards. Copyright © 2013 John Wiley & Sons, Ltd.